Preterm birth during influenza season is associated with adverse outcome in very-low-birth-weight infants - Christoph Härtel; Alexander Humberg; Dorothee Viemann; Anja Stein; Thorsten Orlikowsky; Jan Rupp; Matthias Volkmar Kopp; Egbert Herting; Wolfgang Göpel (Frontiers Media S.A., 2016)
Objective: We investigated the relationship between influenza seasonality and outcome of very-low-birth-weight infants (VLBWI) in a large observational cohort study of the German Neonatal Network (GNN).Materials and Methods: Within the observational period (July 2009 until Dec 2014) 5 influenza seasons occurred (mean duration: 97 days, range: 48-131 days). We stratified VLBWI (n=10187) according to date of birth into three categories; (1) before influenza season, (2) during influenza season and (3) three months after the end of the respective season. Outcomes were assessed in univariate and logistic regression analyses. In a subgroup of infants (n=1497) the number of respiratory infections during the first 24 months of life was assessed.Results: VLBWI born during influenza season carried a higher risk for clinical sepsis (31.0% vs. 28.2%; p=0.014) and periventricular leukomalacia (PVL, 3.7 vs. 2.5%, p=0.004). In a multivariate logistic regression model birth during influenza season was associated with PVL [OR 1.47 (1.11-1.95), p=0.007] and clinical sepsis [OR 1.13 (1.01-1.27), p=0.036], independent of known risk factors, i.e. gestational age, multiple birth, gender and small-for-gestational age. The risk for bronchopulmonary dysplasia was not influenced by influenza seasonality. In the small subgroup with information on 24 months follow-up (n=1497), an increased incidence of common cold and bronchitis episodes was noted in infants born during influenza season.Conclusions: Our observational data indicate that preterm birth during influenza season is associated with PVL and sepsis. These are novel aspects which deserve further investigations to address underlying causes and to include virus surveillance.